HUMAN CAPITAL INVESTMENT: MENINGKATKAN DAYA SAING GLOBAL MELALUI INVESTASI PENDIDIKAN - Ahmad Syamsul Arifin (Institut Pendidikan Tapanuli Selatan, 2023)
Human capital investment is not only believed to be an effort to increase individual knowledge and skills, but also an effort to increase the prosperity of a nation. The government needs to pay serious attention to this problem. This study aims to propose a number of alternative policy steps that can be taken by the Indonesian government to make educational institutions the main sector for optimizing human capital investment. The research method used in this research is a literature study using secondary data as a data source. Based on the studies that have been carried out, there are at least four alternative policy steps that can be taken by the Indonesian government, namely (1) Making long-term investment planning by preparing a human capital investment road map, (2) Making the human capital investment sector one of the main investment priorities (3) Optimizing the absorption of the education budget for expanding access and improving the education system, and (4) Increasing access to foreign technology and ensuring the availability of supporting services for technology development.